Recess Service Innovation Through The Ero'ta Application: Characteristics, Implementation, and Constraints in the Makassar City DPRD - sulmiah, sulmiah; Syahar, Mulyadi; Johansyah, Oky Nur Pratiwi; Widyawati (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2025)
Effective and participatory public services are the key to realizing good governance, especially in the current era of digitalization. This article discusses recess service innovations through the eRO'TA (e-Recess By Us) application at the Makassar City DPRD, which is designed to improve access and transparency in the delivery of people's aspirations. This study aims to analyze the characteristics, implementation, and constraints of the application as a legislative digital innovation model. Using a qualitative approach with a case study design, data was collected through in-depth interviews, participatory observations, and document analysis from 12 key informants. The results of the study show that eRO'TA meets four characteristics of innovation according to Robbins, namely peculiarity, elements of novelty, planned processes, and clear goals. This application has succeeded in increasing the efficiency and accountability of recess services through digital transformation. However, challenges in the form of technical disruptions, lack of socialization, and low digital literacy still hinder widespread adoption. These obstacles have implications for the lack of optimal aspiration databases as the basis for development planning. This study emphasizes that the success of digital innovation in the public sector requires technology integration, institutional readiness, and community empowerment as a prerequisite for participatory and adaptive governance